A Chinese expert consensus on thoracic endovascular aortic repair of type B aortic dissection with a single-branched stent graft for revascularization of the left subclavian artery - Li, Xiaoye; Song, Chao; Zhang, Lei; Yuan, Liangxi; Dai, Xiangchen; Guo, Lianrui; Lu, Qingsheng (Frontiers in Surgery, 2023)
Thoracic endovascular repair (TEVAR) is currently the recommended and most widely used treatment for type B aortic dissection. A major challenge is revascularization of the left subclavian artery in order to extend the landing zone to zone 2 (Ishimaru classification). Various strategies have been used for revascularization, including branched stent graft, fenestrated stent graft, the chimney technique, the parallel technique, and bypass surgery. Single-branched stent graft is one of the most promising strategies, and several products have recently been reported as potential candidates for use with this approach. The Castor single-branched stent graft is the only off-the-shelf product available; this product has been developed through collaboration between Chinese corporations and clinicians. In this Perspective article, clinical experience and data obtained from TEVAR with the Castor single-branched stent graft are summarized by experienced Chinese experts.